Bootstrap-based model selection in subset polynomial regression - Suparman Suparman; Mohd Saifullah Rusiman (International Journal of Advances in Intelligent Informatics, 2018)
The subset polynomial regression model is wider than the polynomial regression model. This study proposes an estimate of the parameters of the subset polynomial regression model with unknown error and distribution. The Bootstrap method is used to estimate the parameters of the subset polynomial regression model. Simulated data is used to test the performance of the Bootstrap method. The test results show that the bootstrap method can estimate well the parameters of the subset polynomial regression model.